Improvement of the surface condition of laser-drilled holes via a dual-wavelength double-pulse train. (January 2023) - Zhang, Shiheng; Fan, Yunru; Huang, Yun; Yang, Xi; Zhang, Meng; Luo, Jieping; Deng, Guangwei; Zhou, Qiang; Song, Haizhi; Wang, You
Highlights: A novel method of laser drilling on stainless steel sheets was shown. Experimental results demonstrated a small front-to-back area ratio. Changes in density around the processing area were analyzed. Simulation results revealed the optimal power combination during laser drilling process. Abstract: Laser drilling is widely used in a variety of applications due to its advantages such as environmental protection, expandability, and non-contact, but still has some drawbacks. One of the most annoying problems is how to improve the surface condition of laser-drilled holes. In this study, we used two nanosecond double-pulse lasers with the wavelengths of 355 and 532 nm to form a combined dual-wavelength double-pulse train for the hole drilling and obtained a series of holes on stainless steel sheets. By using such a dual-wavelength double-pulse train, the area ratio of the front surface to back surface is smaller than those of using both a single-wavelength double-pulse train and a single-pulse laser, and the surface state of drilled holes has not changed significantly. At the same time, the different power components of two pulses have been systematically studied for drilling with a dual-wavelength double-pulse laser. The optimum power ratios of two pulses have been found through a series of experiments. In addition, based on the computation by using an algorithm named as constrained interpolation profile, we theoretically analyzed the changes in density around the processing area for three kinds of lasers during the laser processing. The simulation results show that the dual-wavelength double-pulse approach is the most effective of the hole drilling with a small front-to-back area ratio among three cases. Our results have great potential in the field of laser precision processing.